Making sense of landscape Taylor Cullity Lethlean - Lee, Gini; Ware, SueAnne (Spacemaker Press, LLC, 2013)
Since 1989, Taylor Cullity Lethlean have undertaken an investigation into the poetic expression of the Australian landscape and contemporary culture. This has permeated their design work in a multiplicity of public settings from urban waterfronts to desert walking trails. In each case the detailed exploration of context, site and community have informed outcomes and enriched the patterning and detail of built landscapes. -- From jacket.